Indonesian varsity to honour Dr M.: HONORARY doctorate: Former PM recognised for development of Malay community - Latiff, Rozanna (New Straits Times, 2012)
AN honorary doctorate in humanities and cultural studies will be conferred upon Tun Dr Mahathir Mohamad by Universitas Sebelas Maret (UNS-Solo) today in recognition of his role in the development of the Malay community.